SISTEM PENGAWASAN LEMBAGA PERADILAN DI INDONESIA - Ilmiati, Ilmiati (Bilancia: Jurnal Studi Ilmu Syariah dan Hukum, 2017)
The type of supervision that will be discussed in this paper is the supervision conducted by the judiciary. Indonesia has two judicial institutions that carry out judicial functions. First, namely the Constitutional Court, performs a supervisory function on the performance of the government apparatus in the form of judicial review of the law against the constitution; Secondly, namely the Supreme Court, performs a supervisory function on the performance of the government apparatus in the form of judicial product testing which is hierarchically under the law against the law. In addition, the Supreme Court with a state administrative court structurally under it has the authority to exercise control over decisions or beschikking issued by the state apparatus.